2017
DOI: 10.1163/15709256-12341352
|View full text |Cite
|
Sign up to set email alerts
|

Umbrellas of Conservative Belief: Explaining the Success of Evangelical Congregations in the Netherlands

Abstract: Dutch society is characterized by a high degree of religious dis-affiliation and non-affiliation and most religious communities are facing hard times in the Netherlands. But there are also exceptions. Against the contemporary current of ongoing secularization, some religious communities seem to thrive like never before and even attract new members. But why is that? Why do some religious communities succeed in retaining and also attracting new members while others fail? This article focuses on successful evange… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 14 publications
1
7
0
4
Order By: Relevance
“…Conversion growth in the BFeG is subsiding over the years, from 2.5% in 2003 to 1.9% in 2017, suggesting a drying 'pond' of potential converts in the membership of the larger churches. This lines up well with the observation by Vermeer and Scheepers (2017), that the growth of evangelical churches in the Netherlands largely depends on the availability of orthodox believers in other churches and on the receptivity of the mainstream culture towards evangelical beliefs and values. This does not necessarily affect the growth of individual free churches in every single location, but it will certainly affect the overall growth of free churches if this growth stays dependent on the revivalistic strategy of offering faith renewal to nominal or lapsed Christians.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Conversion growth in the BFeG is subsiding over the years, from 2.5% in 2003 to 1.9% in 2017, suggesting a drying 'pond' of potential converts in the membership of the larger churches. This lines up well with the observation by Vermeer and Scheepers (2017), that the growth of evangelical churches in the Netherlands largely depends on the availability of orthodox believers in other churches and on the receptivity of the mainstream culture towards evangelical beliefs and values. This does not necessarily affect the growth of individual free churches in every single location, but it will certainly affect the overall growth of free churches if this growth stays dependent on the revivalistic strategy of offering faith renewal to nominal or lapsed Christians.…”
Section: Discussionsupporting
confidence: 88%
“…While Christian churches in most European nations have suffered extensively from what can be summarized as 'secularization' , resulting in a massive loss in numbers, the classic free churches (Geldbach 2005;Voigt 2004) seem to have avoided this fate so far. A recent study into thriving evangelical free churches1 in the Netherlands presented them as offering 'protective umbrellas of conservative belief' , allowing them to grow-at least for the time being-even in a very secular context (Vermeer & Scheepers 2017). Also, free churches such as Baptists and Pentecostals have been among the most vigorous planters of new churches, with a strong intention to make converts, achieve church growth, and impact societies (Paas 2016, 61-88).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As we already mentioned in the introduction, the Christian Union is one of the three Christian political parties in the Netherlands and is more left of center, next to the more right wing Reformed Political Party, and the right of center Christian Democratic Party. Not by accident, then, with 53.1% voting for the Christian Union this party is also the most popular political party among our evangelical respondents (Vermeer and Scheepers 2017).…”
Section: Resultsmentioning
confidence: 82%
“…Boersema (2005) calls Dutch evangelicalism a conservative, reactionary movement with a distinctive religious and ethical profile and refers to the establishment of the Evangelical Broadcasting Company, today the biggest religious broadcasting company in the Netherlands, as a milestone in the history of Dutch evangelicalism. More recently, Vermeer and Scheepers (2017) showed that Dutch evangelicalism indeed differs from mainline Christianity in terms of strictness, a striving for religious homogeneity and in terms of specific organizational characteristics that evangelical congregations exhibit. Dutch evangelicals thus also display a kind of subcultural identity as a result of which they may be more oriented towards their own religious networks than to society at large.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%